Determination of the resonance response in an engine cylinder with a bowl-in-piston geometry by the finite element method for inferring the trapped mass. (June 2016) - Broatch, Alberto; Guardiola, Carlos; Bares, Pau; Denia, Francisco D.
Cylinder resonance phenomenon in reciprocating engines consists of high-frequency pressure oscillations excited by the combustion. The frequency of these oscillations is proportional to the speed of sound on pent-roof combustion chambers and henceforth the resonance frequency can be used to estimate the trapped mass, but in bowl-in-piston chambers a geometrical factor must be added in order to deal with the bowl disturbance. This paper applies the finite element method (FEM) to provide a resonance calibration for new design combustion chambers, which are commonly dominated by the bowl geometry near the top dead centre. The resonance calibration does not need any sensor information when it is solved by a FEM procedure, and consequently, is free from measurement errors. The calibration is proven to be independent of the chamber conditions and the results obtained are compared with experimental data by using spectral techniques and measuring precisely the trapped mass.